MOTIVASI MAHASISWA KULIAH SAMBIL BEKERJA (STUDI KASUS MAHASISWA FISIP UNIVERSITAS RIAU) - matussa’ Diah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study trying to uncover the motivation student work. The phenomenon of students who college while working nothing new among students. The phenomenon of students who college while working on the found in the Campus FISIP Riau University in Pekanbaru City. A variety of reasons background students who college, work is a factor economic, a time, and want to be independent. Based on the phenomenon on, then the formulation of the problem ia about the reason student work, allocation time between the college and work, and family background student work. The theory in use this study is the theory Need For Achievement to David McClelland and theory Motivation to Maslow. The research in use is Snowball Sampling, then the number of the subject there are 8 subject students FISIP. The results of research suggest is motivation to work that a student is a factor economic, a time, and want to be independent to improve the quality of what to do subject, also to plan what would in do after it, that inisiation career could continue in develop and recognize the potential away from each of the subject.Keywords : Motivation, College, Work